Strength Variable Analysis With the Height of Body Mass Center In High Spike Position 4 In Volleyball League Players - Hamid, Huda (Journal of Physical Education, 2016)
The importance of the research lies in studying and analyzing jumping skill variables in volleyball to identify the percentage of their effect on spiking in volleyball. In addition to that the importance lies in using modern technology and programs that will help both coach and player in identifying the factors that affect his performance. The aims of the study are; identifying the muscular strength values taking from the foot scan as well as identifying the height of body's center of weight for volleyball players during spiking and finally the research aimed at identifying the relationship between strength and height on jump in volleyball spiking.The researcher sued the descriptive method. The subjects were (9) volleyball players who are good in spiking and they are all from the Iraqi national team season 2015 – 2016. The main experiment was conducted on Sunday 27/3/2015 at three o'clock in the college of physical education and sport sciences volleyball court / University of Baghdad